2012
DOI: 10.1137/120872164
|View full text |Cite
|
Sign up to set email alerts
|

Point Measurements for a Neumann-to-Dirichlet Map and the Calderón Problem in the Plane

Abstract: This work considers properties of the Neumann-to-Dirichlet map for the conductivity equation under the assumption that the conductivity is identically one close to the boundary of the examined smooth, bounded and simply connected domain. It is demonstrated that the so-called bisweep data, i.e., the (relative) potential differences between two boundary points when delta currents of opposite signs are applied at the very same points, uniquely determine the whole Neumann-to-Dirichlet map. In two dimensions, the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…An early result for the linearized problem in an annular domain in R 2 with no measurements on the inner boundary is in [Hä98]. In the case when the conductivity is known near the boundary, the partial data problem can be reduced to the full data problem [Is88], [AU04], [Fa07], [Be09], [AK12], [HPS12]. Also, we remark that in the corresponding problem for the wave equation, it has been known for a long time (see [KKL01]) that measuring the Dirichlet and Neumann data of waves on an arbitrary open subset of the boundary is sufficient to determine the coefficients uniquely up to natural gauge transforms.…”
Section: Introductionmentioning
confidence: 99%
“…An early result for the linearized problem in an annular domain in R 2 with no measurements on the inner boundary is in [Hä98]. In the case when the conductivity is known near the boundary, the partial data problem can be reduced to the full data problem [Is88], [AU04], [Fa07], [Be09], [AK12], [HPS12]. Also, we remark that in the corresponding problem for the wave equation, it has been known for a long time (see [KKL01]) that measuring the Dirichlet and Neumann data of waves on an arbitrary open subset of the boundary is sufficient to determine the coefficients uniquely up to natural gauge transforms.…”
Section: Introductionmentioning
confidence: 99%
“…Theorem 2.1 allows one to extend the partial data result [21] for Calderón problem to piecewise smooth plane domains: This can be generalized as follows Theorem 2.3. Let Γ, Ξ be (possibly disjoint) countably infinite subsets of ∂D.…”
Section: Setting and Main Resultsmentioning
confidence: 97%
“…The following two lemmas state the relationship between the weak formulations presented above and a distributional Sobolev space formulation based on trace theorems, utilized in, e.g., [21]. Proof.…”
Section: 2])mentioning
confidence: 99%
“…Remark 4.1. In [17,31] it has been shown that M (σ ε ) = 0 if and only if σ ε = σ 0 (≡ 1) when the number of electrodes is countably infinite in two dimensions. Here, we have demonstrated that one can constructively find σ ε ≡ σ 0 such that M (σ ε ) = 0 in case the number of electrodes is finite.…”
Section: Construction Of Invisible Conductivities In Two Dimensionsmentioning
confidence: 99%
“…All these articles assume the Cauchy data for (1) are known on all of ∂D, but the partial data problem of having access only to some subset(s) of ∂D has also been tackled by many mathematicians; see, e.g., [19,20] and the references therein. From our view point, the most important uniqueness results are presented in [17,31] where it is shown that any two-dimensional conductivity that equals a known constant in some interior neighborhood of ∂D is uniquely determined by the PEM measurements with countably infinite number of electrodes. This manuscript complements [17,31] by constructively showing that for an arbitrary, but fixed and finite, electrode configuration there exists a perturbation of the unit conductivity that is invisible for the EIT measurements in the framework of the PEM.…”
Section: Introductionmentioning
confidence: 99%